Masonry - Parkinson, G. (Thomas Telford, 1996)
This guide provides practical advice and guidance on the repair and maintenance of masonry structures. It covers all of the various forms of masonry, including stone, brick and blockwork.
At foot of t.p.: Curtins Consulting Engineers.
Keywords: Masonry -- Maintenance and repair.; elektronické knihy; electronic books